COMPARISON OF SIX BIOASSAY METHODS FOR THE ASSESSMENT OF CARBFURAN SUSCEPTIBILITY OF Faustinus apicalis (FAUST) - BORRERO-FONSECA, FABIOLA; ZENNER DE POLANÍA, INGEBORG (Revista Colombiana de Entomología, 1991)
Adults of Faustlnus apicalis (Faust) (Coleoptera:Curculionidae), not subject to selection pressure by insecticides, were used to compare six bioassay methods to test susceptibility to insecticides in curculionids under laboratory conditions, involving carbofuran as the standard insecticide. The methods tested at the Entomological Laboratory at CI 'Tibaitatá" were: Topical application with technical grade and commercially formulated insecticide, dip test, exposure to residues on filter paper, and exposure te residues on glass with commercial formulation and technical grade insecticide. The results of these experiments were judged on the basis of assay validity, sensitivity and efficiency; optimal exposition time was also evaluated. All bioassays were performed with both males and females. Results indicated that the most precise method to test susceptibility in F. apicalis and other curculionids with similar characteristics is a topical application with commercially formulated insecticidal. Optimal exposure time to insecticide before mortality evaluation was standardized at 72 hours. Males were slightly more susceptible than females; therefore the use of females is recommended.